Immunopathogenesis and Treatment of Rheumatoid Arthritis: Recent Developments - Giasuddin, ASM; Jhuma, KA; Haq, AMM; Haque, MM (Bangladesh Journal of Medical Biochemistry, 2015)
Rheumatoid arthritis (RA) is a chronic inflammatory disease occurring three times more in females throughout the world affecting 1-2% of the adult population in all ethnic groups, usually in the age group of 25-60 years. Although the role of CD4 + T helper lymphocytes in the aetiopathogenesis has been studied for more than three decades, the focus on CD4 + T helper type 17 (Th17) lymphocytes and its associated cytokines is much more recent. The cytokines such as IL-17 and IFN-g induce secondary cytokines such as IL-1, TNF-a , etc which possibly cause inflammation in joints. This cytokine cascade, therefore, offers a number of points and opportunities for immunointervention in RA. The present review article highlights some of the major aspects of the immunopathogenesis that involve Th17 cells and their association relevant to recent developments in the treatment of RA. DOI: http://dx.doi.org/10.3329/bjmb.v7i2.22415 Bangladesh J Med Biochem 2014; 7(2): 62-67